The bacterial Sec-translocase: structure and mechanism - Lycklama, J.A.; Driessen, A.J.M.
Most bacterial secretory proteins pass across the cytoplasmic membrane via the translocase, which consists of a protein-conducting channel SecYEG and an ATP-dependent motor protein SecA. The ancillary SecDF membrane protein complex promotes the final stages of translocation. Recent years have seen a major advance in our understanding of the structural and biochemical basis of protein translocation, and this has led to a detailed model of the translocation mechanism.
Keywords: PROTEIN TRANSLOCATION; MEMBRANE PROTEIN INSERTION; SECY; TRANSLOCON; SECA